Israf's Behavior Towards The Use Of Pay Later In The Practice Of Selling And Purchasing In The Marketplace - Setiawan Bin Lahuri; Indah Taqiyah Mabarroh; Atina Rahma Mawaddah (IQTISHADequity jurnal MANAJEMEN, 2022)
The current development of e-commerce is followed by the development of payment methods for transactions. The majority of payment methods provided by e-commerce are digital payments, one of which is currently developing is paylater. The presence of the paylater feature makes online transactions more efficient and provides many conveniences. Finally increasing the consumer behavior of people in shopping that is close to waste. Waste in Islamic scholarship is a form of israf and tabdzir which is prohibited by religion because it can cause harm to humans. The purpose of this paper is to describe indications of israf behavior caused by paylater services. The writing method used is to use a normative approach, namely by approaching the problem based on the principles of Islamic Shari'ah and Islamic law. Then the analytical method used is a qualitative method, through an inductive mindset (specific to general), namely by analyzing the ideas and methodological framework of Islamic law which then draws general conclusions. The results of the study concluded that the existence of paylater payment services available in the marketplace can encourage someone to behave extravagantly which is in line with the concepts of israf and tabdzir in Islam. Convenience, bonuses, and paylater promotional services lead to impulse buying which makes a person shop not based on need, but on the basis of desire. This is one of the characteristics of israf and tabdzir behavior that is in accordance with the review of Surah al-A'raf Verse 31 and Surah Al-Isra` verses 26-27. The existence of this relevance provides information that encourages paylater users to be more careful in shopping and managing finances in order to avoid israf and tabdzir behavior which is prohibited by Islam